Biodiversity update — Progress in taxonomy - Blackmore, Stephen (Himalayan Journal of Sciences, 2006)
Taxonomy and systematics underpin our ability to conserve and benefit from biodiversity in sustainable ways as envisaged under the Convention on Biological Diversity (CBD). Despite progress in phylogenetics towards reconstructing the “Tree of Life” and in biodiversity informatics, the fundamental documentation of species necessary to complete the inventory of life has lagged behind. It is argued that this reflects a lack of appreciation of the role played by species-level taxonomic information in underpinning conservation and sustainable use and under-investment in the relevant institutions at the expense of supporting the centralised financial mechanism of the CBD. This article is reprinted with permission from Science, Volume 298, Issue 5592, page 365. Copyright © 2002 by The American Association for the Advancement of Science. All rights reserved. Full text in the print version of the journal. Himalayan Journal of Sciences 1(2): 83-84, 2003